THE ERROR ANALYSIS OF ARABIC GRAMMAR IN THE KALAMUNA BOOK - Mamnunah, Mamnunah; Abdurrahman, Maman; Sopian, Asep (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2021)
This article aimed to analyze the forms of Qawa’id Nahwu's mistakes in the Kalamuna book published by Sabilillah Sampang Islamic Boarding School specifically to improve the abilities of the maharatul kalam. This book consists of various everyday expressions, vocabulary and short stories as well as some debate themes. For beginners who are just learning Arabic, they will always remember the first thing they learned and will always be guided by everything that is learned from the basics. This study used a descriptive method with an error analysis approach (Tahlīl al-Akhtha') while the results of this study show there are errors in Qawa’id Nahwu in the form of Maf'ul Bih, Na'at Man'ut, Ism Ghayr Munsharif, al-Hal, Idhafah, Khabar Kana. Thus, this article can be used as an evaluation and material for consideration for publishers in order that these mistakes do not take root among the students.